The contribution of self-regulation and youtube users to risky sexual behavior for boarding house students - Riski Pratiwi; Mudjiran Mudjiran (Journal of Counseling and Educational Technology, 2020)
Early adulthood is a time when students tend to want to know something new, including sexual behavior, the lack of information about the sexual behavior makes students engage in risky sexual behavior.The factors for risky sexual behavior are self-regulation and YouTube users.The purpose of the study is to describe the contribution of self-regulation to risky sexual behavior, the contribution of self-regulation to risky sexual behavior, and the contribution of both variables to risky sexual behavior. The population in this study was 330 students in the eastern freshwater villages of Padang city and a sample of 60 people using purposive sampling techniques.The instruments used were self-composed instruments, namely self-regulation instruments, YouTube users and risky sexual behavior using a Likert scale model.Data Scale model analyzed with quantitative descriptive methods, simple regression, and multiple regression. Analysis of the data showed that there was a self-regulation contribution to risky sexual behavior by 70%, YouTube users' contribution to risky sexual behavior by 74%,  contribution self-regulation and YouTube users'  to risky sexual behavior by 77.4%.Based on the results of this study can later develop a program or technique in guidance and counseling that can assist students in avoiding risky sexual behavior.